Comparison of Neuropsychological Functioning Between Adults With Early- and Late-Onset DSM-5 ADHD. Issue 1 (January 2020) - Lin, Yu-Ju; Gau, Susan Shur-Fen
Objective: We aimed to compare the visually dependent neuropsychological functioning among adults with Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) ADHD who recalled symptom onset by and after age 7 and non-ADHD controls.Method: We divided the participants, aged 17 to 40 years, into three groups—(a) ADHD, onset <7 years (early-onset, n = 142); (b) ADHD, onset between 7 and <12 years (late-onset, n = 41); (c) non-ADHD controls ( n = 148)—and compared their neuropsychological functioning, measured by the Cambridge Neuropsychological Testing Automated Battery.Results: Both ADHD groups had deficits in attention and signal detectability, spatial working memory, and short-term spatial memory, but only the early-onset group showed deficits in alertness, set-shifting, and planning after controlling for age, sex, and psychiatric comorbidities. There was no statistical difference between the two ADHD groups in neuropsychological functioning.Conclusion: DSM-5 criteria for diagnosing adult ADHD are not too lax regarding neuropsychological functioning.